Evaluation of Heavy Metals Concentration in Street, Storm and Suspended Dust in Al-Zafaraniya Area, Baghdad- Iraq - Aljewari, Azhar F.M.; Al-Salman, Ibrahim M.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The current study was applied in Al-Zafaraniya area southeast of the capital Baghdad from October 2021 to April 2022. This is to evaluate some heavy elements (Cd, Co, Cu, Fe, Pb, and Mn) in the street, storm, and suspended dust. Four sampling sites were selected, and codes A, B, C, and D were given to represent the industrial activity sites, service workshops, business activity, and residential areas.        The results showed that the concentration rates of elements (Cd, Co, Cu, Fe, Pb, Mn) in street dust samples were (1.15, 6.6, 60.15, 26770, 44.4, 6, 489.8). In storm dust (2, 10, 49.3, 54760, 24.3, 827.2) ppm, respectively, the results of suspended dust revealed that the general rates of element concentrations were (0.707, 3.546, 3.727, 83.204, 1.076, 8.706) μg/m3, respectively. The results also showed the frequency of the appearance of the same elements and different concentrations in the three types of dust. They also indicate that each other interacted in increasing and continuing to expose the city atmosphere to the air loaded with hazardous metals to the health of human society and the components of the city's ecosystem.   It can also be concluded from the values and variations of the elements that there are several environmental factors, such as temperature, humidity, air currents, local and regional storm surges, and irregular distribution of vegetation, can be attributed to the main reason in the deference values of heavy elements and their presence in the street, storm and suspended dust